Condiciones socioeconómiias de los minadores chamberos y propietarios de centro de acopio del cantón Pasaje, en el periodo 2012-2011 - Carmona Banderas Icta, Marlene Beatriz (2012)
The issue is of major importance because it seeks to provide opportunities to improve living conditions and prevent the workers miners, chamberlings and owners of collection centers and their family continue to be mistreated and socially injured.